Survey of less Invasive Surfactant Administration in England, slow adoption and variable practice. (16th September 2019) - Bhayat, Sadaf; Kaur, Avineet; Premadeva, Irnthu; Reynolds, Peter; Gowda, Harsha
Abstract: Aim: National survey to evaluate the uptake of Less Invasive Surfactant Administration (LISA) in neonatal units across England. Methods: A web‐based survey was sent out by email to all 150 neonatal units in England. It consisted of questions regarding indications for LISA, the practicalities of the procedure and reasons for not using this technique. Results: The response rate was 96% (144/150 units). Only 11% of units are using LISA, but majority (78%) would consider implementing LISA on their unit. 56% would also consider LISA on delivery suite. Challenges identified are having a guideline and staff training. 61% of units have set the target population ≥27 weeks. On sub‐analysis, for tertiary units, the trend for LISA is ≥26 weeks. The median FiO2 threshold for LISA is 0.3 (IQR 0.3‐0.4) in less than 28 weeks gestational age (GA), and 0.4 in higher gestations. The most common suggestion for premedication is fentanyl (32%). Conclusion: The uptake of LISA in England is low comparing to the rest of Europe. Even though many units are considering implementing LISA, there is lack of training and national guidelines. There is urgent need for standardisation of practice and clear indications for LISA.